Evaluation of Caesalpinia pulcherrima endospermic gum as affinity matrices for galactose-binding lectins interaction - Braga,Renata Chastinet (2011)
Lectins are proteins or glycoproteins able to bind, specifically and reversibly carbohydrates and glycoconjugates. Considering this ability, the utilization of Caesalpinia pulcherrima seeds polysaccharides as an affinity matrix was tested. The endospermic gum were solubilized in distinct concentrations of NaOH and treated with different amounts of epichlorohydrin (ECH) forming affinity gels with variable capacity for interaction with galactose- binding lectins. The gel with an ECH/gum ration of 6.0mmol/g was selected as the best affinity matrix. The matrix presented different efficiencies in terms of isolating galactose-binding lectins. C. pulcherrima endospermic galactomannans were purified by ethanol precipitation and the purified galactomannan was crosslinked with the best formulation of gel. The Artocarpus incisa, Ricinus communis and Abrus precatorius lectins showed interactions of 11.5, 17.7 and 47.2mg of retained protein in 1g of gel, respectively; the Artocarpus integrifolia lectin showed the highest affinities (79.7mg/g). The heamaglutination assays confirmed the activity and SDS-PAGE electrophoresis confirmed the isolation of the lectins in a single-step procedure.